Three-pass laser welding of Ti alloy-stainless steel using Nb and Ni interlayers - Yan Zhang; JianPing Zhou; DaQian Sun; HongMei Li (Journal of Materials Research and Technology, 2020)
Nb:YAG laser welding of TC4 titanium (Ti) alloy and 301 L stainless steel (SS) were carried out through interlayers Nb and Ni. The laser beam was concentrated at the Ti alloy-Nb interface, Nb-Ni interface and Ni-SS interface, respectively, to ensure that whole Nb and Ni interlayer was not melted. Three-pass welding was employed, which involves the creation of a joint with three welding zones separated by the remaining unmelted Nb and Ni. Interlayer Nb and Ni were employed to prevent the formation of Ti-Fe intermetallics and improve the microstructure and the properties of the Ti alloy-SS joint. The joint fractured at the welding zone of the Nb-Ni interface with the tensile strength of 269 MPa. Keywords: Interlayer, Welding, Microstructure, Tensile strength